THE COSTS OF A RENEWABLE-ENERGY BASED ELECTRICITY SUPPLY SYSTEM ON JAVA AND BALI - Matthias Günther (Prosiding Seminar Nasional Pakar, 2018)
There is a growing consciousness about the necessity to transform our energysupply systems into more sustainable systems. In particular the usage ofrenewable energy resources comes to the fore. However, sometimes it is stillconsidered to be a question of costs whether the transition of the energysystems to more sustainable ones should be realized in a near future or ratherlater. The present study examines the costs of an electricity supply based onexclusively renewable resources in the Java-Bali grid. It argues that within thequite manageable time horizon of 30 years (target year 2050) electricitygeneration costs can be achieved that are competetitive with currentgeneration costs in many countries. This is a strong argument to pursue thegradual restructuring of the electricity generation system towards arenewable-resource based one.